IMPACT OF PROGRESSIVE MUSCLE RELAXATION AND AROMATHERAPY ON MENSTRUAL PAIN INTENSITY AMONG ADOLESCENT GIRLS WITH PRIMARY DYSMENORRHEA - Astuti, Erlina Suci; Solikhah, Fitriana Kurniasari; Prahasti, Azizah Ayu; Ciptaningtyas, Maria Diah (SYNTIFIC, 2025)
Background. Primary dysmenorrhea, characterized by cramping pain during menstruation, significantly affects adolescents' quality of life. The purpose of this study was to evaluate the effects of progressive relaxation exercise and aromatherapy on pain intensity in female adolescents with primary dysmenorrhea. ResearchMethod. A total of 64 participants were divided into four groups: progressive relaxation, aromatherapy, combination therapy, and control. The research method used is a quasi-experimental pretest-posttest control group design. This study employs the Paired T-Test on the third treatment group, and the NGain-Score test is used to determine which independent variable is more closely related to the dependent variable. Findings. Statistical analysis showed significant reductions in pain intensity in all experimental groups (p = 0.000), with the combination therapy demonstrating the highest effectiveness (NGain-Score: 0.7571). Aromatherapy, particularly with lavender, and progressive relaxation exercises effectively reduced physical discomfort and psychological stress associated with dysmenorrhea. The findings suggest that non-pharmacological interventions, especially when combined, are effective in managing dysmenorrhea. Conclusion. Integrating progressive relaxation exercise and aromatherapy is a promising approach for alleviating primary dysmenorrhea pain in adolescents, offering a safe and natural alternative to conventional pain management.